DISTRIBUSI ALOKASI SUMBER DAYA DALAM RUMAH TANGGA DI INDONESIA: ANAK SEKOLAH ATAU BEKERJA? - Wiwin Setyari Ni Putu (Puslit Kependudukan dan Pengembangan SDM Universitas Udayana, 2013)
Rotten Kid theorem of Gary Becker asserts that if all members of the family received the gift or income of other household members , then even if there are family members who are selfish , they still will maximize total family income . Thus, the welfare of the family members will not be affected at anyone who holds power in the family because of the assumption of homogeneous preferences (unitary approach) . However, these assumptions can be said to be unrealistic , especially recent studies in collective models show systematic differences between the way men and women distribute its power in the household . This paper tries to analyze the behavior of households in Indonesia in distributing the resources they have, especially in determining the child’s human capital formation . Utilizing data from IFLS4 , it can be said in Indonesian households in general have an allocation system that is unitary approach . Distribution is done together does not depend on who holds the power in it . In particular also an indication that the higher the wife’s education , the better the child’s education and are owned by the decline in the probability of child labor .